ACCESSIBILITY OF TRANSPORTATION FACILITIES FOR DISABILITIES (CASE STUDY OF TRANS SEMARANG) - Suwandi, Putri Anggi Permata; Saputro, Bayu Singgih; Hermanto, Wilarso; Kristiawan, Agung (International Journal of Sustainable Building, Infrastructure and Environment (IJOSBIE), 2020)
Accessibility related to public transport is a means of advancing the economic welfare of the community, creating and increasing economic degrees, as well as a precursor sector of other sectors. Therefore, people with disabilities are also entitled to the same service to the public transportation as an effort to realize similarities, the equality of citizens and the enhancement of the role of disability. This research aims to analyse disability access and the role of the transportation service of Semarang and PT. Trans Semarang on Bus Rapid Transit in Semarang City. This research uses a type of qualitative approach that is implemented through interviews, observations and documentation. The conclusion of this research shows that from the regulatory aspects, the government of Semarang should be appreciated because the government of Semarang has tried to fulfill the rights of the disabled. But from the implementation aspect, there needs to be an improvement because the accessibility of disabled people running optimally can be seen through the condition of public facilities in the city of Semarang. Public facilities in the city of Semarang do not completely ignore the reference accessibility means there are public facilities that have been good enough but many more are not optimal.